Risk Assessment of Hazardous Materials Transportation with Fuzzy Fine Kinney and Fuzzy AHP Methods - Erkuvun, Kubra Sezen; Usta, Selcan; Guneri, Ali Fuat (WORLD SCIENTIFIC PUBL CO PTE LTD, 2026)
This study seeks to prioritize risks by implementing a hazardous materials transportation risk assessment approach. A three-stage risk assessment method is proposed for the transportation processes of fuel oil, one of the hazardous materials. Fuzzy Fine Kinney and fuzzy analytical hierarchy process (AHP) methods were used in the study. The risk scores were first fuzzified to eliminate the disadvantages of the Fine Kinney method. The fuzzy Fine Kinney risk scores were insufficient for prioritization, and the steps of the fuzzy AHP method were applied by creating a hierarchical structure for hazards with equal scores. Finally, the importance levels of all hazards were determined. According to the risk assessment results, the hazard of failure to comply with weather conditions and legal speed limits while driving has the highest level of importance. Risk control measures for high severity of this hazard were prioritized by fuzzy AHP method. As a result of the application, the measure of instantly checking that vehicles are moving by speed rules with the vehicle tracking system was prioritized. According to the evaluation, it was concluded that the hazards of high importance are primarily driver-related, i.e., human-related. As a result, this study contributes to the prioritization of fuel transportation hazards.
Keywords: Fuel transportation; fuzzy AHP; fuzzy Fine Kinney; risk assessment; hazardous materials; DECISION; Engineering